LEGAL PROTECTION OF THE TRADEMARK RIGHTS IN LICENSE AGREEMENT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Under Regulation 207/2009 / EC, a licensee which is not registered in asuitable register cannot initiate proceedings due to a violation oftrademark rights. The subject of this analysis is how the courts in theMember States of the European Union are acting on this issue, i.e. howthey apply Article 23 paragraph 1 of Regulation 207/2009 / EC.Firstly, authors are analysing the issue concerning the rights of thelicensee which has not been registered in an appropriate register has in theevent of a violation of a trademark right. The authors endeavour to reexaminethe uniqueness of acting in practice in a way that would encirclea research process and would see flaws in the normative regulation of thesame.Considering that in practice there are cases in which, according to Article23, paragraph 1 of the Regulation, the courts in the Member States of theEuropean Union adopt different judgement, the case of the analyse is thejudgment of the European Court of Justice C-163/15.The aim of this paper is to point out that only through an efficient systemof protection and proper implementation of the legislation, taking intoaccount the practice of the European Court of Justice will contribute to thestabilization of the economic circulation of goods and services.